Implementasi Asesmen Perkembangan Sosial Emosional Anak Usia 5-6 Tahun - Meluh; Saudah; Aghnaita (Ihya Ulum: Early Childhood Education Journal, 2023)
The development of students does not only aim to know the growth and development listed on report cards, anecdotes but also the characteristics of unique and rapid development, AI-Ukhuwah Islamic Kindergarten is one of the kindergartens in Palangka Raya City which has implemented the 2013 Curriculum and assessments on 6 aspects of child development, one of which is social emotional. This study aims to describe the implementation of the assessment of social emotional development of children aged 5-6 years at Al-Ukhuwah Islamic Kindergarten Palangka Raya. The primary data source of this research uses qualitative methods of secondary data sources with a descriptive approach. The subjects were a Group B teacher and 15 students, as well as the Head of Al-Ukhuwah Islamic Kindergarten Palangka Raya as informants. Data extraction using observation, interview and documentation techniques validated by using triangulation of techniques and sources. Furthermore, it was analyzed with 4 stages, namely data collection, data reduction, data presentation and conclusion drawing. The results showed that the implementation of the assessment of the social emotional development of children aged 5-6 years at Al-Ukhuwah Islamic Kindergarten Palangka Raya, carried out by teachers with the process of determining the aspects or areas to be evaluated, collecting data or information relevant to the problem, conducting assessments, interpreting and determining strategies, implementing or implementing strategies that have been selected and evaluating progress.